2019
DOI: 10.1016/j.heliyon.2019.e02888
|View full text |Cite
|
Sign up to set email alerts
|

Explanations around physical abuse, neglect and preventive strategies among older Yoruba people (60+) in urban Ibadan Southwest Nigeria: A qualitative study

Abstract: Older people's views, experiences and explanations on abuse and neglect in later life is marginal in the literature. With more cases of physical abuse and neglect in old age in sub-Saharan Africa, this study explored the views and positions of older people and community stakeholders like religious leaders on why physical elder abuse and neglect and preventive measures within community settings in Nigeria. An exploratory research design that consisted of two focus group discussions with older Yoruba men and wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The victim profile was observed to be women with severe physical and cognitive disability (17) . This study's findings have shown that there was a significant association between risk of violence and being a female, reaffirming previous studies (6,(17)(18) . Although distinct, since violence against the elderly involves intergenerational relations and violence against women relates to gender issues, both aggressions are based on asymmetric power relations and may be associated.…”
Section: Resultssupporting
confidence: 90%
“…The victim profile was observed to be women with severe physical and cognitive disability (17) . This study's findings have shown that there was a significant association between risk of violence and being a female, reaffirming previous studies (6,(17)(18) . Although distinct, since violence against the elderly involves intergenerational relations and violence against women relates to gender issues, both aggressions are based on asymmetric power relations and may be associated.…”
Section: Resultssupporting
confidence: 90%
“…Later life in Nigeria is branded with many difficulties of which poverty is supreme ( Boyi, 2019 ; Adisa, 2019 ). This is because many of the older persons do not have the needed energy to cater for their daily needs, thus depending on their children and grandchildren for their daily essentials ( Adisa, 2019 ; Agunbiade, 2019 ). Social security that is available in most western nations for older adults is lacking in Nigeria ( Anifalaje, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overall effect is seen in the level of satisfaction with life among older persons. The situation is far worrisome in Nigeria rural communities where basic social amenities and essentials of life are lacking ( Tanyi et al., 2018 ; Mobolaji et al., 2018 ; Agunbiade, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, there are virtually no theory-based explanations of what causes institutional abuse and neglect of older adults [ 7 ]. Evidence shows that the reported prevalence of domestic EA is lower compared to institutional homes and care facilities [ 3 ]. The reported prevalence of institutional EA is heavily underestimated and amounts to only 20% of the true prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers, clinicians, and health policymakers have acknowledged EA as a major threat to the health and Open Access *Correspondence: sakineh_gholamzadeh@yahoo.com well-being of older adults [2]. This social phenomenon can occur within families as well as therapeutic relationships in hospitals and institutional settings such as nursing homes, residential care, and daycare facilities [3,4]. However, one of the main concerns in taking care of older patients is the occurrence of EA in hospitals and institutional settings [4][5][6].…”
Section: Introductionmentioning
confidence: 99%